Simulation of the Holocene climate over South America and impacts on the vegetation - Maksic, Jelena; Shimizu, Marilia Harumi; Oliveira, Gilvan Sampaio de (sage, 2019)
We provide a comprehensive analysis of the Holocene climate and vegetation changes over South America through numerical simulations. Holocene climate for several periods (8 ka, 6 ka, 4 ka, 2 ka, and present) were simulated by an atmospheric general circulation model, forced with orbital parameters, CO2 concentrations, and sea surface temperature (SST), while the analysis of the biome distributions was made with a potential vegetation model (PVM). Compared with the present climate, our four simulated periods of the Holocene were characterized by reduced South Atlantic Convergence Zone intensity and weaker South American Monsoon System (SAMS). The model simulated conditions drier than present over most of South America and gradual strengthening of SAMS toward the present. The Northeast Brazil was wetter because of southward migration of the intertropical convergence zone (ITCZ). Moreover, SST conditions were the main forcing for the climate changes during the mid Holocene inducing larger austral summer southward ITCZ migration. PVM paleovegetation projections are shown to be consistent with paleodata proxies which suggest fluctuations between biomes, despite the fact that ages of dry/wet indicators are not synchronous over large areas of the Amazonian ecosystem. Holocene PVM simulations show distinct retreat in Amazonian forest biome in all four simulated periods. In 6 ka, present caatinga vegetation in Northeastern Brazil was replaced with savanna or dense shrubland. The simulations also suggest the existence of rainforest in western Amazonia and the expansion of savanna and seasonal forest in the eastern Amazon, with shifts in plant community compositions and fragmentation located mostly in ecotone regions. Moreover, our PVM results show that during the Holocene, the Amazonian tropical forest was smaller in area than today, although western Amazonia persisted as a tropical forest throughout the Holocene.
Keywords: caatinga; climate change; ITCZ; monsoon; paleovegetation; potential vegetation; rainforest; savannah